GAYA BAHASA SINDIRAN IRONI, SINISME DAN SARKASME DALAM BERITA UTAMA HARIAN KOMPAS - Agus Heru (Jurnal Pembahsi (Pembelajaran Bahasa Dan Sastra Indonesia), 2018)
The problem of this research is how the use of sarcasm, sarcastic and sarcasmic sarcasm in Kompas April 2015 headlines and whether the contents of the protests contained in Kompas headlines in April 2015 are reviewed based on political elements. The purpose of this study describes the use of sarcastic, sarcastic and sarcastic sarcasm styles contained in the headlines in Kompas daily in April 2015 and describes the contents of the protest contained in the headlines in the April 2015 Kompas newspaper reviewed based on political elements. Theoretically this research is expected to contribute to the theory of language style satire of irony, cynicism and sarcasm in relation to political protests. It is practically useful as one of the alternatives in Teaching Indonesian about the use of sarcastic, sarcastic and sarcastic sarcasm styles in fiction and non fiction. The method used is descriptive. Source of data in this research is derived from Kompas political news in April 2015. Political news that was studied was taken from Kompas daily for one month from 1-30 April 2015. While the data analysis techniques used content analysis techniques and change analysis techniques. The results show the use of sarcastic, sarcastic and sarcasmic sarcasm style which contains political protests in Kompas headlines in April 2015 consisting of replacement elements and replaceable elements that have similarities in semantics, categories, or analogies. The use of sarcastic, sarcastic and sarcastic sarcasm in the headlines of Kompas daily in April 2015 amounted to 17 sarcasm, sarcastic and sarcasmic sarcasm. In this regard, there is a need for further efforts to introduce analytical teaching of a kind of sarcastic, cynicism and sarcasm Keywords— Language style satire of irony, cynicism and sarcasm